2021
DOI: 10.1101/2021.04.09.439067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of endogenous miRNA reference genes across different zebrafish strains, developmental stages and kidney disease models

Abstract: The majority of kidney diseases arise from the loss of podocytes and from morphological changes of their highly complex foot process architecture, which inevitably leads to a reduced kidney filtration and total loss of kidney function. It could have been shown that microRNAs (miRs) play a pivotal role in the pathogenesis of podocyte-associated kidney diseases. Due to their fully functioning pronephric kidney, larval zebrafish have become a popular vertebrate model, to study kidney diseases in vivo. Unfortunate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…CircRNAs involved in stroke also have a wide range of mechanisms, including DNA inactivation, methylation, transcriptional promotion, activation of other RNA molecules, and so on (Bauer et al, 2022;Meng et al, 2022). Moreover, scientists have found that circRNA can undergo various epigenetic modi cations, including methylation and ubiquitination, and act as ceRNA with some microRNAs (miRNAs) to form a regulatory network (Siegerist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs involved in stroke also have a wide range of mechanisms, including DNA inactivation, methylation, transcriptional promotion, activation of other RNA molecules, and so on (Bauer et al, 2022;Meng et al, 2022). Moreover, scientists have found that circRNA can undergo various epigenetic modi cations, including methylation and ubiquitination, and act as ceRNA with some microRNAs (miRNAs) to form a regulatory network (Siegerist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%